Edukasi Dampak Narkoba terhadap Fisik, Perilaku, Serta Emosional di MTS/MA Miftahul Ulum Gisting Atas Tanggamus - Sulastri Sulastri; Murni Lestari; Halimah Tusa’Diah; Alvi Mevia Elbatista; Supriyadi Supriyadi; Akhmad Hadi Parlaungan; Clara Meigia Putri (Universitas Muhammadiyah Manado, 2024)
Drug use among teenager is increasing, teenagers or early adulthood are very liable (vulnerable) to negative influences from the surrounding environment, including invitations to try drugs. The effects of drug use are not only physical, but will also have an impact on the behavior and emotions of the user. The aim of holding this socialization activity to prevent drug abuse is to provide comprehensive education in the school environment, because educational institutions are one of the places where teenagers spend most of their time. The method used for socialization at MTS/MA Miftahul Ulum is an interactive lecture and discussion method, with material presented in the Microsoft Word Power Point (PPT) application. The socialization was carried out in a conducive and focused manner, and received a positive response from the school, and students were seen to have begun to understand and realize the dangerous effects of using drugs.